Updated Anopheles mosquitos abundance and distribution in north-eastern malaria-free area of Argentina - MARINA STEIN; MÍA E. MARTIN; PATRICIA G. RAMÍREZ; EDUARDO G. ETCHEPARE; GRISELDA I. ORIA; GUSTAVO C. ROSSI; JORGE KURUC; ELIZABET L. ESTALLO (Anais da Academia Brasileira de Ciências, 2024)
Abstract Malaria is the most important parasitic disease worldwide. In 2019, more than 679,441 cases of malaria were reported in the American region. During this study, Argentina was in malaria pre-elimination autochthonous transmission phase with the aim of being declared as malaria-free country. The aim of this work was to assess the influence of remote sensing spectral indices (NDVI, NDWI) and climatic variables (temperature, relative humidity and precipitation) on the distribution and abundance of Anopheles mosquitoes, in four localities with different degrees of anthropogenic disturbance and with previous malaria cases records located , in a historical malarious area in northeastern of Argentina. Between June 2012 and July 2014, mosquitoes were collected. We collected 535 Anopheles adult mosquitoes. Anopheles strodei s.l. was the most abundant species. The greatest richness, diversity and abundance of species were registered in wild and semi-urban environments. The abundance of Anopheles presented a negative association with relative humidity and mean temperature, but positive with mean maximum temperature. The most important variables determining Anopheles total abundance and distribution were NDWI Index and distance to vegetation. The abundance of An. strodei s.l., was positive associated with water areas whereas the NDVI Index was negatively associated.